Analysis Of Student Constraints In Online Biology Learning During The Covid-19 Pandemic - Tasya Hudia; Rahmawati Darussyamsu (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2021)
The Covid-19 pandemic has an impact on almost all aspects of life, one of which is education. One of the efforts made by the government in the education aspect is the implementation of online learning. Changes in learning methods that were originally carried out offline or face-to-face to online learning experienced several constraints in the implementation process for both teachers and students. This study aims to determine the constraints of high school students in online biology learning during the Covid-19 pandemic. The type of research conducted is descriptive research with a sample of students of class XI and XII MIPA at SMA Excellent Nurul Ikhlas. The data collection technique in this study used a survey technique using an instrument in the form of a questionnaire given to 40 students. The data analysis technique used in this research is descriptive analysis. The results showed that the percentage of constraints experienced by students in the implementation of online biology learning, namely: (1) quota and internet network 40%, (2) communication limitations 25%, (3) difficulties in understanding material 25%, and (4) lack of focus/tasks accumulate 10%. Based on the results of data analysis, it can be concluded that the biggest obstacles experienced by students in online learning at SMA Excellent Nurul Ikhlas are quotas and internet networks.